Persepsi Kelangkaan, Urgensi dan Kualitas Produk terhadap Keinginan Membeli Skincare G2G Melalui Live Tiktok: Studi Kasus Pada Mahasiswa Universitas Teuku Umar - Cindy oktavia sihombing; Cut Mega Putri; Muhammad Rahmat Hidayat; Ivon Jalil; Rusdi Rusdi (Jurnal Publikasi Ilmu Manajemen, 2026)
This study aims to analyze the contribution of perceived scarcity, perceived urgency, and product quality to consumers' purchase intention toward G2G skincare products through TikTok live streaming. This research employed a quantitative approach with a sample of 200 students from Teuku Umar University selected using purposive sampling technique. Data were collected through a Likert-scale questionnaire. Descriptive analysis, validity testing, and reliability testing were conducted using R Studio, while the relationships among variables were analyzed using the Simplified Random Forest method with TIBCO Statistica. The results showed that the Simplified Random Forest model demonstrated good predictive ability with an explained variance value of 56.51%. All independent variables contributed to consumers' purchase intention. Product quality was the most dominant factor with an importance value of 1.000000, followed by perceived urgency at 0.851117, and perceived scarcity at 0.661773. These findings indicate that the better the product quality offered through TikTok live streaming, the higher the consumers' desire to purchase, while urgency and scarcity strategies also play a role in increasing buying interest. The consistency of these findings is reinforced by the Stimulus-Organism-Response (SOR) theoretical framework, in which product quality serves as the strongest stimulus in shaping purchasing responses.